Transition and justice : negotiating the terms of new beginnings in Africa - Anders, Gerhard; Anders, Gerhard; Zenker, Olaf (USA Wiley Blackwell, 2015)
"This book examines a series of cases where peaceful 'new beginnings' have been declared after periods of violence and where transitional justice institutions played a role in defining justice and the new socio-political order"--
Keywords: Peace-building -- Africa -- Case studies; Transitional justice -- Africa -- Case studies; Truth commissions -- Africa -- Case studies; POLITICAL SCIENCE / Economic Conditions